2017
DOI: 10.5897/ajps2016.1464
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of common bean (Phaseolus vulgaris L.) varieties in Raya Valley, Northern Ethiopia

Abstract: Phaseolus vulgaris L. (Leguminosae) is a crop widely distributed in all parts). Therefore, Nasir variety was well performed to Raya Valley condition. Therefore, this variety has to be promoted in farmers field for dissemination and scaling up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 4 publications
8
4
0
Order By: Relevance
“…The result also showed that significant differences were observed among the common bean varieties for days to maturity (Table 1). This finding is in agreement with the previous works (Tekle et al, 2014;Gereziher et al, 2017;Dembele and Ashenafi, 2018;Yohannes et al, 2020;Temesgen and Zewdu, 2021). The number of days to attain physiological maturity ranged from 86.25 days for the variety Wajo to 95.88 days for the variety ROR1 (Table 2).…”
Section: Resultssupporting
confidence: 94%
“…The result also showed that significant differences were observed among the common bean varieties for days to maturity (Table 1). This finding is in agreement with the previous works (Tekle et al, 2014;Gereziher et al, 2017;Dembele and Ashenafi, 2018;Yohannes et al, 2020;Temesgen and Zewdu, 2021). The number of days to attain physiological maturity ranged from 86.25 days for the variety Wajo to 95.88 days for the variety ROR1 (Table 2).…”
Section: Resultssupporting
confidence: 94%
“…In this study, the means and ranges of phenological traits and yield-related traits, such as the number of PPP, the number of SPP, HSW, and SW, revealed a wide range of genetic variation. A high phenotypic variation for these traits in the common bean was also reported by different authors [10,[18][19][20][21][22][23][24]. The high phenotypic variation observed in this study may be attributed to the genetic variations among the genotypes and the environmental variations in the tested locations.…”
Section: Agronomic Performancesupporting
confidence: 84%
“…This was also confirmed by other researchers that the Ethiopian common bean landraces were represented by high phenotypic diversity [ 3 , 10 , 24 ]. Similarly, the common bean grown in different parts of the world revealed a significant variation in yield and yield-related traits [ 18 , 20 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…(2014) reported that Sedi variety yielded a shelled seed of 2042–2944 kg ha −1 in eastern and southern Ethiopia, which is in contrast to the present findings. The significance of yield trait has been reported by many authors in different legume crops, such as groundnut ( Amare and Tamado, 2014 ; Biru and Daraje, 2014 ; Aliyi, 2017 ; Wedajo and Wondewosen, 2017 ), common bean (Demelash et al., 2016; Teame et al., 2017 ), faba bean ( Wondimu, 2016 ), chickpea ( Yasin et al., 2017 ). A significant difference was observed between varieties in days to flowering and physiological maturity as presented in Table 3 .…”
Section: Resultsmentioning
confidence: 85%